The Occurrence and Pathological Characterization of Rust Causing Fungi of Brachiaria Grass in Kenya - Cherunya, J. A.; Kipsumbai, P. K.; Rop, N. (African Journal of Education,Science and Technology (AJEST), 2019)
Brachiaria grass is one of the most important grasses distributed throughout the tropics especially in Africa. The quality of forage yields and biomass of brachiaria is negatively affected by diseases among which leaf spot, leaf blight and leaf rust are the most common. This research was conducted to characterize the rust pathogen of brachiaria grass infected selected genotypes in Kenya based on pathological and morphological characteristics. Leaves with leaf rust pustules were collected from improved cultivars and natural population from brachiaria production and demonstration plots at the International Livestock Research Institute, Nairobi, Kenya. Pathogenicity of rust isolates was determined on the brachiaria cultivars in glasshouse. The growth conditions of rust pustules were determined by exposing into different regimes of relative humidity, temperature and time to germ tube development were established under rust ideal environmental conditions. The cultivars tested (MG4, Piata, Xareas and Marandu) were susceptible to rust diseases in the field as well as in controlled environment. In the field the percent disease incidence of 100% was recorded while disease severity was higher in MG4 (7.5 and 8.5) in 2016 and 2017, respectively in a disease severity scale of 0 to 9. The disease was least severe in Piata (2.5) in 2016 and in Marandu (3.0) in 2017. Under artificial inoculation and controlled growth conditions MG4 proved more susceptible (6.5) while, Piata (1.7) was less severe in glasshouse. However, under growth chamber Xareas was most affected with a disease score of 6.5. The isolate from MG4 was more virulent on MG4 than isolates obtained from other bracharia cultivars followed by isolates from Xareas , which caused disease severity of (3.5) on MG4. When the isolates were subjected to different environmental conditions it was established that optimum relative humidity of 75% and temperature of between 20-250C was ideal for germ tube germination. Germ tube germination started after the 8th hour but stopped extending at the 24th hour. Morphologically the isolates varied in spore size from 20µm to79µm and in spore shape which were oval or globose, but all were yellow in colour. These findings indicated high occurrence of leaf rust disease in bracharia cultivars with varying tolerance levels which can provide a potential source of resistance genes. Further it is advisable to institute control measures against leaf rust whenever relative humidity is above 75% and temperature of 20-250C prevails.